Hegemony of Saudi Arabia's Kafala System in The Relationship Between Employer and Indonesian Female Domestic Migrant Workers 2018-2020 - Karin Caroline Kelly; Uliviana Restu; Ika Arinia Indriyany (International Journal of Social Sciences Review, 2022)
This study describes the hegemony produced by the Saudi Arabian state through the kafala system in the relationship between employers and female migrant domestic workers from Indonesia. The kafala system creates many problems due to the structural dependence between domestic migrant workers and their employers, ranging from heavy workloads and irregular wages to restrictions on access to mobility. Employers as individual sponsors have a large dominance of power so that the working conditions for domestic migrant workers become unbalanced. This study is analyzed using Antonio Gramsci's hegemonic perspective with three indicators of understanding, namely the ruling class, defense of the domination of the ruling class, and the crisis of ruling class hegemony. This study was dissected using a qualitative critical approach. This study indicates that the hegemony in this research phenomenon belongs to a declining level of hegemony characterized by the potential for disintegration hidden beneath the surface. Various restrictive Saudi Arabian regulations hamper the awareness of civil society, which has been gradually awakened. The limitations of civil society on access to participatory democracy have resulted in mass resistance to the Kafala system not coming to the surface.